Calorie Intake Monitoring Application Using the Mifflin–St Jeor Algorithm - Ariyo Aziz Pratama; Joko Aryanto (Kirana Publisher (KNPub), 2025)
Unbalanced dietary habits are a major factor contributing to health issues such as obesity, malnutrition, and metabolic disorders. These problems often arise from the lack of awareness of daily energy needs, leading to uncontrolled calorie intake. This study aims to develop a calorie monitoring application that assists users in managing their nutritional balance accurately and efficiently. The system implements the Mifflin–St Jeor algorithm to calculate daily energy requirements based on user data, including age, gender, height, and weight. Body Mass Index (BMI) and Total Daily Energy Expenditure (TDEE) are integrated to provide adaptive calorie recommendations according to each user’s activity level. The application was developed using Flutter for the mobile interface and Flask as the backend framework. Validation testing showed a deviation of less than 1% between manual and system calculations, confirming the algorithm’s accuracy and reliability. The results demonstrate that the developed system can deliver personalized and precise calorie recommendations while supporting continuous monitoring of food intake. This approach enables users to maintain energy balance and achieve specific health goals such as weight loss, maintenance, or gain.